Hubungan Usia dan Paritas Ibu dengan Kejadian Berat Badan Lahir Rendah (BBLR) - Maifitri, Elsi; Rahmi, Sania Lailatu; Bachtar, Fitrina (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2025)
Low Birth Weight (LBW) is one of the leading causes of neonatal mortality and contributes to the incidence of stunting, hypoglycemia, hypothermia, and immunological disorders in infants. The main risk factors for LBW include maternal age, parity, poor nutritional status, and pregnancy complications. This study aims to determine the relationship between maternal age and parity with the incidence of LBW at Ibnu Sina Islamic Hospital in Bukittinggi City in 2024. This research is a quantitative study with a cross-sectional design. The study was conducted from January to June 2025 with the population consisting of all mothers who gave birth at Ibnu Sina Islamic Hospital in Bukittinggi in 2024. The sampling technique used was simple random sampling, with a total of 92 mothers who met the inclusion criteria. Data were obtained from medical records and analyzed using the Chi-Square test. The results showed that most respondents were of non-risk age (83.7%) and had risk-level parity (59.8%). The incidence rate of LBW was recorded at 40.2%. Bivariate analysis showed no significant relationship between maternal age (p = 0.398) or maternal parity (p = 0.143) and the incidence of LBW. In conclusion, there was no significant relationship between maternal age or parity and the incidence of LBW in this study. However, the relatively high incidence of LBW indicates the need for ongoing interventions. It is hoped that the results of this study will improve screening for the causes of LBW among healthcare workers and provide input for healthcare workers to further explore the factors that contribute to LBW.